1999
DOI: 10.1080/10556699.1999.10603410
|View full text |Cite
|
Sign up to set email alerts
|

College Freshmen Smokers versus Nonsmokers: Academic, Social, and Emotional Expectations and Attitudes toward College

Abstract: I n September 1996, 544 college freshmen completed a 142-item survey assessing their academic, social, and emotional expectations of college and attitudes toward cigarette smoking. Differences were explored based on gender and smoking status. Twenty-seven percent (n=148) were smokers, 58% (12=86) o f w h o m were female. Chi-square analyses revealed several significant relationships. Smokers rated themselves significantly higher than nonsmokers in several measures of academic performance, including reading sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The influence of high‐school friends' smoking behavior, college friends' smoking behavior, and fathers' smoking behavior was supported by this study. Hines et al (1998) and Spencer (1999) found that having an increased number of college friends who smoked was a significant risk factor for college smoking and is consistent with the findings of this study. It is interesting to note the difference in the number of close friends who smoked, as they moved from high school to college.…”
Section: Discussionsupporting
confidence: 90%
“…The influence of high‐school friends' smoking behavior, college friends' smoking behavior, and fathers' smoking behavior was supported by this study. Hines et al (1998) and Spencer (1999) found that having an increased number of college friends who smoked was a significant risk factor for college smoking and is consistent with the findings of this study. It is interesting to note the difference in the number of close friends who smoked, as they moved from high school to college.…”
Section: Discussionsupporting
confidence: 90%
“…At other times, occasional smoking is defined by the frequency of the behavior during the past month. Occasional smoking has been defined as smoking every week but not every day (Hines, Fretz, & Nollen, 1998), 1 day per week or less (Spencer, 1999), and between 4 and 20 days in the past month (Turner, Veldhuis, & Mermelstein, 2005). Another problem with occasional (and social) smoking is that large portions of these smokers have no intention of quitting, believe they have already quit, or do not perceive themselves as smokers (Koontz et al, 2004;Morley, Hall, Hausdorf, & Owen, 2006;Waters, Harris, Hall, Nazir, & Waigandt, 2006).…”
Section: Introductionmentioning
confidence: 99%